HEART RATE VARIABILITY BASED DRIVER DROWSINESS DETECTION: DETEKSI KANTUK PENGEMUDI BERBASIS VARIABILITAS DETAK JANTUNG - Naba Ali Maktouf; Sajid Saleh Khalaf (Journal of Medical Genetics and Clinical Biology, 2024)
Driver drowsiness may cause traffic injuries and death. Various methods have been given to detect drowsiness, for instance, image-based biometric-signals-based. In this project, a new approach using heart rate and head tilt is discussed. The aim of the project is to provide a device with simple components that enables the driver to save his life by avoiding accidents caused by frequent sleepiness by giving a sound alert (alarm), which forces the driver to wake up and regain control of the car This device is not considered a treatment for the problem of sleep, but rather a preventive tool from accidents daily the project was designed with simple components, the most important of which are (ECG sensor and acceleration sensor Arduino, alarm device). ECG sensor: it used to give an ECG signal to Arduino to analysis it. ADXL335 sensor: it is placed behind the driver's head. This sensor senses the fall of the driver's head when he sleeps. It was added to sense better.